Electron microscopy of whole cells in liquid with nanometer resolution - de Jonge, N. (National Academy of Sciences, 2009)
Single gold-tagged epidermal growth factor (EGF) molecules bound to cellular EGF receptors of fixed fibroblast cells were imaged in liquid with a scanning transmission electron microscope (STEM). The cells were placed in buffer solution in a microfluidic device with electron transparent windows inside the vacuum of the electron microscope. A spatial resolution of 4 nm and a pixel dwell time of 20 μs were obtained. The liquid layer was sufficiently thick to contain the cells with a thickness of 7 ± 1 μm. The experimental findings are consistent with a theoretical calculation. Liquid STEM is a unique approach for imaging single molecules in whole cells with significantly improved resolution and imaging speed over existing methods.